Genetic diversity and phylogenetic relationship of Chinese cashmere goats based on microsatellite DNA markers - Di, R.; He, X.; Guan, Wei-Jun; Pu, Y.; Zhao, Qianjun; Fu, B.; Ma, Y.; Han Jianlin (Science China Press., Co. Ltd., 2007)
Genetic diversity of nine indigenous Chinese cashmere goat populations and one West African breed were investigated using 19 microsatellite DNA markers and fluorescence PCR. The aim was to investigate the status of the genetic resources of Chinese cashmere goats. Fourteen of the microsatellite loci were highly polymorphic and effective markers for analysis of genetic diversity and relationship among goat populations. Analysis of polymorphic information content and genetic heterozygosity showed that the Chinese goat populations have high genetic diversity. Both UPGMA dendrogram and scatter plots of estimates from principal component analyses showed that the Chinese and African goat populations belong to different clades. Among the Chinese goat populations the Hegu and Hexi populations were genetically more distant from the other goat populations. The remaining seven Chinese goat populations were clustered into two clades. The first clade contained Liaoning, Xinjiang, Chaidamu and Shanbei goat populations, while the sec-ond clade was made up of goat populations from Inner Mongolia. These results may provide a scientific basis for the characteristization, conservation and utilization of Chinese cashmere goats.